2005
DOI: 10.1080/10408440591007412
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action: Yolk Sac Poisoning and Impeded Histiotrophic Nutrition—HBOC-Related Congenital Malformations

Abstract: Rodents form an early inverted yolk sac placenta (invYSP) by apposing the yolk sac to the uterine wall. The invYSP supplies nutrients via histiotrophic nutrition involving pinocytosis of materials from uterine gland secretions, lysosomal degradation, and transfer of the products to the embryo. Interference with histiotrophic trafficking through the invYSP by high-molecular-weight molecules (such as trypan blue) causes malformations and resorptions. Later in gestation, rodents form a definitive chorioallantoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…More recent WEC research by Ambroso and Harris has suggested that the mechanism by which the anti-malarial drug and in vivo teratogen, chloroquine, acts is via reversible inhibition of cysteine proteinase cathepsin B and L activity (Ambroso and Harris, 1994). These studies on histiotrophic nutrition are critically important for human risk assessment, as there is considerable evidence suggesting that this mechanism occurs only in species that rely on an inverted yolk sac placenta during organogenesis, but not in humans and other primates that utilize a chorioallantoic placenta throughout gestation (Beck, 1976;Carney et al, 2004;Holson et al, 2005).…”
Section: Yolk Sac As a Target For Teratogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…More recent WEC research by Ambroso and Harris has suggested that the mechanism by which the anti-malarial drug and in vivo teratogen, chloroquine, acts is via reversible inhibition of cysteine proteinase cathepsin B and L activity (Ambroso and Harris, 1994). These studies on histiotrophic nutrition are critically important for human risk assessment, as there is considerable evidence suggesting that this mechanism occurs only in species that rely on an inverted yolk sac placenta during organogenesis, but not in humans and other primates that utilize a chorioallantoic placenta throughout gestation (Beck, 1976;Carney et al, 2004;Holson et al, 2005).…”
Section: Yolk Sac As a Target For Teratogenesismentioning
confidence: 97%
“…This key early placental nutrition transfer pathway involves endocytic uptake of proteins by the visceral yolk sac, degradation by lysosomal cysteine proteases, and delivery of amino acids to the embryo via the vitelline circulation. The classic compound acting via this mechanism is trypan blue, although other agents acting similarly include anti-VYS antibodies, anti-laminin antibodies, somatomedin inhibitors, a class of compounds known as hemoglobin-based oxygen carriers, dextran, and chloroquine (Brent et al, 1990;Chambers et al, 1995;Fisher, 1981;Holson et al, 2005;Hunter et al, 1991).…”
Section: Yolk Sac As a Target For Teratogenesismentioning
confidence: 98%
“…O saco vitelino invertido de roedores desempenha vá-rias funções podendo-se destacar aquelas relacionadas ao armazenamento, absorção e transferência de nutrientes (Laliberté et al 1984, Carter 2001, Holson et al 2005, Favaron et al 2012. De fato, distúrbios nestas funções produzidas por agentes teratogênicos, por exemplo, podem explicar possíveis doenças no recém-nascido (Jollie 1990).…”
Section: Introductionunclassified
“…The mode of action (MoA) for several adverse developmental outcomes has been determined , Foster 2005, Holson et al 2005, Kavlock and Cummings 2005. The regulatory guideline and MoA toxicity studies with sulfoxafl or described above revealed fi ndings for which an MoA had not previously been described (Rasoulpour et al 2012).…”
Section: Dammentioning
confidence: 99%
“…Recent eff orts have also been directed toward extending the MoA approach to non-cancer MoA analyses , Foster 2005, Holson et al 2005, Kavlock and Cummings 2005, with several addressing human relevance. Standardization of the approach has also been recommended by the IPCS (Boobis et al 2008).…”
Section: Dammentioning
confidence: 99%